2016
DOI: 10.22359/cswhi_7_2_05
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome in neurological nursing

Abstract: Abstract:Objective: To ascertain the incidence of burnout syndrome in Nurses working in Neurological Nursing. Burnout Syndrome (SV) often occurs in Neurological Nursing, where the Nurses are in circumstances associated with suffering and death. Design: For the diagnosis of burnout syndrome we used the Maslach Burnout Inventory (MBI). Respondents consisted of Nurses n = 120 working at the Neurological Department, in a hospital and ambulances belonging to those wards in Slovakia. Results: In our study, out of n … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 7 publications
1
5
0
Order By: Relevance
“…In our sample of nurses, we recorded a medium to high burnout level with the CBI. This is also pointed out by other studies (Slezáková et al, 2015;Pilárik & Tobákošová, 2013), which also identified a medium to high burnout rate in 50-90% of cases of nurses in Slovakia (using the Maslach Burnout Inventory questionnaire). The issue of the shortage of nurses on the labor market, their excessive workload, and burnout has a chronic character in Slovakia.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…In our sample of nurses, we recorded a medium to high burnout level with the CBI. This is also pointed out by other studies (Slezáková et al, 2015;Pilárik & Tobákošová, 2013), which also identified a medium to high burnout rate in 50-90% of cases of nurses in Slovakia (using the Maslach Burnout Inventory questionnaire). The issue of the shortage of nurses on the labor market, their excessive workload, and burnout has a chronic character in Slovakia.…”
Section: Discussionsupporting
confidence: 68%
“…Negative associations have also been identified between patient safety and adverse outcomes in nursestheir professional burnout, and lower job satisfaction and well-being (Alves & Guirardello, 2016;Hall et al, 2016;Liu et al, 2018;Vifladt et al, 2016). The healthcare system in Slovakia, as in other countries, struggles with a lack of registered nurses, due to job dissatisfaction, increased migration (Gurková et al, 2013(Gurková et al, , 2020, and burnout (Pilárik & Tobákošová, 2013;Slezáková et al, 2015). Monitoring the patient safety grade and patient safety climate from nurses' perspectives, as well as other factors (job satisfaction, burnout syndrome), has been shown to be vital for improving patient safety (Gurková et al, 2020;Kirwan et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Slezáková et al. ( 2015 ) assessed the occurrence of burnout among 120 neurological nurses. Medium degrees of EE and DP were reported among 28% ( N = 34) and 37% ( N = 44) of nurses respectively.…”
Section: Discussionmentioning
confidence: 99%
“…This may be because the authors used differing research tools. For example, while some studies (Akman et al., 2016 ; Gallagher & Gormley, 2009 ; García‐Izquierdo & Ríos‐Rísquez, 2012 ; Jiang et al., 2016 ; Liakopoulou et al., 2008 ; Moussa & Mahmood, 2013 ; Purvis et al., 2019 ; Slezáková et al., 2015 ; Wang et al., 2019 ) used Maslach Burnout Inventory (MBI), others (Kupcewicz & Jóźwik, 2019 ) used the Copenhagen Burnout Inventory (CBI), and still others (Jiang et al., 2016 ) used the authors’ questionnaire. Other important factors influencing the differences in the prevalence of burnout may be different work practices applied and recommended in different countries, different in‐hospital procedures, work organization, interpersonal relations, cultural differences or the size of the sample—the last of which differed across studies, ranging from 49 (Purvis et al., 2019 )–over 1,800 nurses (Kupcewicz & Jóżwik, 2019 ; Wang et al., 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Those who score 0-6, 7-12 and ≥ 13 on the depersonalisation dimension have low, moderate and high levels of depersonalisation, respectively. Items measuring lack of personal accomplishment are reverse-coded; participants with scores of 0-31, 32-38 and ≥ 39 exhibit high, moderate and low lack of personal accomplishment, respectively [13].…”
Section: Maslach Burnout Inventory (Mbi)mentioning
confidence: 99%